Farm to factory : women's letters, 1830-1860 - Dublin, Thomas, 1946- (New York : Columbia University Press, 1993)
Relates the experiences of women who left the farms they were raised on to work in the New England textile factories before the Civil War.
The Hodgdon letters -- Letters to Sabrina Bennett -- The Larcom letters -- Mary Paul letters -- Delia Page letters.
Includes bibliographical references and index.
Reference and Research Book News.
Young Adult
Keywords: Women textile workers -- New England -- Correspondence; Women -- Employment -- New England -- History; Women -- New England -- Correspondence; Women textile workers -- Correspondence; Women -- Correspondence; Women -- Employment